Callus induction and regeneration of date palm (Phoenix dactylifera L.) cv. Zambli through somatic embryogenesis from four layers of young leaves explant - Masna Maya Sinta; Rizka Tamania Saptari; Imron Riyadi; Sumaryono Sumaryono (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2024)
The Zambli variety of date palm shows potential for cultivation in tropical regions, as its fruits are edible during the Rutab stage. However, large-scale production of Zambli seedlings presents a significant challenge. In vitro propagation offers a solution for producing large quantities of clonal planting material. This study focuses on inducing callus formation from the four-layered shoot tips of young leaves and regenerating these calli into plantlets through somatic embryogenesis. Explants were cultured on a modified MS medium with 10, 50, or 100 mg L-1 2,4-dichlorophenoxyacetic acid (2,4-D), combined with 1 or 3 mg L-1 N6-(2-isopentenyl)adenine (2-iP). Embryo maturation was performed on the same medium without 2,4-D, while a hormone-free medium was used for plantlet regeneration. The results indicated that the highest callus induction occurred from the younger leaf layer (layer 1) in the medium containing 100 mg L-1 2,4-D and 1 mg L-1 2-iP, achieving a callus formation rate of 82.3%. Successful callus induction was achieved from the first, second, and third layers of young leaves. Somatic embryo maturation and plantlet regeneration were also completed, producing vigorous, well-rooted plantlets. Additionally, the development of date palm cv. Zambli in vitro culture through somatic embryogenesis was confirmed through histological analysis.